Pusat Pelatihan Penanggulangan Bencana Di Riau Dengan Pendekatan Eko Arsitektur - Ahmed, Heyder; Rijal, Muhammad; Firzal, Yohannes (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Mitigation is an effort in the face of natural disasters, prevent and reduce casualties. Itrequired trained personnel who are ready to get down to the field who have specialized knowledgeand skills in the field of mitigation. Disaster Management Training Center in Riau is designed as aplace of education, training, and recreation in the field of disaster mitigation. This training centeraccommodate all disaster simulation activities either indoor or outdoor. The Disaster ManagementTraining Centre approaches Eco Architecture as the design theme. Not only space in outer spacebut also applying the principles of Eco Architecture. Disaster Management Training Centre toapply the concept of solidarity and humanity are qualities that should be possessed by humans.Solidarity and Humanity selected as a draft so that this region can later make a high level ofawareness of fellow human beings. Disaster Management Training Center in Riau has fourbuilding mass by applying the concept of solidarity and humanity as the basis for the formation andbuilding mass. Access the mass of the building's four interconnected in order to strengthen theconcept of solidarity and humanity in the draft. For the space in the building for DisasterManagement Training Centre has many openings that provide natural lighting effects andpenghawaan into buildings.Keyword: Mitigation, Disaster Management Training Center, Solidarity and Humanity.